ANALISIS TEORI SOSIOLOGI OLAHRAGA TERHADAP NILAI SPORTIVITAS DALAM KEHIDUPAN MAHASISWA - Tommy Situmorang; Yan Indra Siregar; Putra Arima; Astrid l Br Purba; Sukri; Bagus Eka Setiawan; Imel Tiansih Wau; Angelika Ginting; Jumadi; Rifky Fahren Siambaton; Joel Sinaga; Dio Reza Arfansyah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The sociology of sport is a branch of science that studies the relationship between sporting activities and social life. In a university environment, sport plays a crucial role in shaping student character, particularly the value of sportsmanship. Sportsmanship reflects honesty, discipline, responsibility, respect for opponents, and upholding the rules of the game. This article aims to analyze the sociology of sport theory in relation to the value of sportsmanship in student life. The method used is a qualitative descriptive study through a literature review of various journals and scientific books. The results of the discussion indicate that functionalism theory, conflict theory, and symbolic interactionism theory have a close relationship in shaping students' sportsmanship behavior through sporting activities. The value of sportsmanship can increase social solidarity, cooperation, and self-control in students' academic and social lives.